(untitled) (UNWE Yearbook, 2022)
Tax penalty proceedings are part of the tax procedure. Its legal framework is regulated in the Tax and Social Insurance Procedure Code (TSIPC) and Administrative Violations and Sanctions Act (AVSA). Hence, the proceedings are normatively established and realized mainly in two phases. The first is associated with the ascertainment of tax violation and the issuance of an instrument on the ascertainment of such an offence. The second encompasses the imposition of the respective sanction, which materializes in the issuance of a penalty decree.